Ekosida: Studi Atas Pendekatan Loss Of Ecological Service Dan Environmental Crime Serta Prospek Pengaturan Di Indonesia - Triantono, Triantono; Purwanti, Ani; Rochaety, Nur (Jurnal Hukum & Pembangunan, 2022)
Ecosides have become an international discourse since the 1970s, as a result of concerns about human behavior towards the environment. In the last 10 years ecocide has appeared so clearly as part of a structured, systematic and massive exploitative action. The development of environmental crimes in the form of ecocides has not been followed by concrete efforts in the form of an international consensus to define ecocides as the most serious crime that can threaten environmental destruction. In the midst of this situation, there are 2 (two) interesting approaches to be developed further within the framework of explaining, analyzing and understanding ecocides, namely the loss of ecological service and environmental crime approaches. Therefore this study will focus on 2 (two) issues, : What is the history, concept and significance of ecocides in the framework of environmental protection and human rights; and what about ecocide analysis in the loss of ecological service and environmental crime approaches in the dimensions of international criminal law and reform of Indonesian criminal law? The results of the study show that formulating ecocides as a normative construct is very important in order to provide further steps in protecting both the environment and humans. The duality of approaches in understanding ecocide has the opportunity to be developed in the context of an integrative approach, thereby guaranteeing certainty of response to ecocide internationally, including in developing effective criminal policies in Indonesia.